Regenerative Medicine: A Review of the Evolution of Autologous Chondrocyte Implantation (ACI) Therapy - Rebecca L Davies; Nicola J Kuiper (Bioengineering, 2019)
Articular cartilage is composed of chondrons within a territorial matrix surrounded by a highly organized extracellular matrix comprising collagen II fibrils, proteoglycans, glycosaminoglycans, and non-collagenous proteins. Damaged articular cartilage has a limited potential for healing and untreated defects often progress to osteoarthritis. High hopes have been pinned on regenerative medicine strategies to meet the challenge of preventing progress to late osteoarthritis. One such strategy, autologous chondrocyte implantation (ACI), was first reported in 1994 as a treatment for deep focal articular cartilage defects. ACI has since evolved to become a worldwide well-established surgical technique. For ACI, chondrocytes are harvested from the lesser weight bearing edge of the joint by arthroscopy, their numbers expanded in monolayer culture for at least four weeks, and then re-implanted in the damaged region under a natural or synthetic membrane via an open joint procedure. We consider the evolution of ACI to become an established cell therapy, its current limitations, and on-going strategies to improve its efficacy. The most promising developments involving cells and natural or synthetic biomaterials will be highlighted.